Electronic and steric structure “Quasi-verdazyls.” I. Phosphaverdazyl and its leuco base - Nesterenko, A.; Polumbryk, Oleg; Markovskii, Leonid (My University, 1984)
By the PNDO method in an spd basis, with complete optimization of geometry, the electronic and steric structure has been calculated for different conformers of a model phosphaverdazyl and its leuco base. The results are consistent with the interpretation given previously for the ESR spectra of phosphaverdazyls. Features of electronic structure are judged in terms of their influence on the physicochemical properties and reactivity of phosphatetrazines.
Keywords: фосфафердазил; PNDO; phosphaverdazyl; кафедра харчової хімії